Implications of Perhutani's CANOPY Brand Use for Nature Tourism After Trademark Registration Rejection by DGIP - Ratna Laniati; Dewi Sulistianingsih; Rini Fidiyani (The Indonesian Journal of International Clinical Legal Education, 2024)
Perum Perhutani has experienced an increase in tourism, necessitating standardization through the "Canopy" certification as a management guideline. This is regulated under the Decree of the President Director of Perhutani Number 2026/KPTS/DIR/2017 concerning the Standardization of Nature Tourism Management for Perum Perhutani, aimed at improving product and service quality, preserving forest sustainability, and benefiting the community. However, the "Canopy" service mark proposed by Perhutani was rejected by DJKI. The rejection was based on the similarity in pronunciation and type of goods with the registered mark "The Canopy." In fact, the two marks operate in different fields: "Canopy" for tourism services (class 39) and "The Canopy" for stationery (class 16). Thus, their products do not directly compete. The rejection of the "Canopy" mark is considered inconsistent with Article 21 of Law Number 20 of 2016 on Trademarks and Geographical Indications. The absence of legal action from Perhutani has resulted in the inability to use the mark, as it risks violating Article 100 paragraphs (1) and (2) of the same law. This research employs a juridical-empirical method with a qualitative approach through observation, interviews, documentation, and literature review. The findings indicate that Perhutani has complied with Article 5 paragraph (1) of the Regulation of the Minister of Tourism and Creative Economy Number 27 of 2014 concerning Recreational Park Business Standards through the "Canopy" certification. This has provided ecological, social, and economic benefits, as well as improved facilities and services. The rejection of the "Canopy" mark has caused financial losses at several tourist locations. Rebranding cannot proceed without a replacement name, causing the standardization program for nature tourism management to halt. The researcher recommends that Perhutani promptly create a replacement name for the certification so that the standardization program can continue and be applied to other Perhutani tourist destinations.